A discrete-time framework for proximate time-optimal performance of damped servomechanisms. (June 2016) - Flores, J.V.; Salton, A.T.; Gomes da Silva Jr., J.M.; Neto, N.B.; Chen, Z.
Abstract: This paper proposes nonlinear control strategies for the discrete-time near time-optimal control of damped servomechanisms. Both the well established Proximate Time Optimal Servomechanism (PTOS) and its dynamically damped version (ddPTOS) are extended for damped systems. Stability results are presented in a general discrete-time framework suitable for both damped and undamped systems. These results allow the reduction of constraints in the traditional PTOS – particularly regarding the acceleration discount factor – while encompassing the nonlinear damping of the ddPTOS. Experimental results demonstrate the efficiency of the proposed controllers.